2015
DOI: 10.1107/s1399004715001005
|View full text |Cite
|
Sign up to set email alerts
|

A noncanonical PWI domain in the N-terminal helicase-associated region of the spliceosomal Brr2 protein

Abstract: The spliceosomal RNA helicase Brr2 is required for the assembly of a catalytically active spliceosome on a messenger RNA precursor. Brr2 exhibits an unusual organization with tandem helicase units, each comprising dual RecA-like domains and a Sec63 homology unit, preceded by a more than 400-residue N-terminal helicase-associated region. Whereas recent crystal structures have provided insights into the molecular architecture and regulation of the Brr2 helicase region, little is known about the structural organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…Consistent with Brr2 held in an inhibited state, human tri-snRNP preparations are stable in the presence of ATP, 94 indicating that the human tri-snRNP structure represents a resting state of the tri-snRNP before delivery to the spliceosome. Furthermore, in full agreement with the suggested role as a multi-protein interaction device and as an anchor to the tri-snRNP, 54,55 the Brr2 NTR interacts with several other proteins in the human tri-snRNP, with the plug contacting Prp6 and the RH domain of Prp8 and the PWI domain interacting with Snu114 and Sad1 (Fig. 4B).…”
Section: Brr2 Regulation In the Tri-snrnpsupporting
confidence: 57%
See 3 more Smart Citations
“…Consistent with Brr2 held in an inhibited state, human tri-snRNP preparations are stable in the presence of ATP, 94 indicating that the human tri-snRNP structure represents a resting state of the tri-snRNP before delivery to the spliceosome. Furthermore, in full agreement with the suggested role as a multi-protein interaction device and as an anchor to the tri-snRNP, 54,55 the Brr2 NTR interacts with several other proteins in the human tri-snRNP, with the plug contacting Prp6 and the RH domain of Prp8 and the PWI domain interacting with Snu114 and Sad1 (Fig. 4B).…”
Section: Brr2 Regulation In the Tri-snrnpsupporting
confidence: 57%
“…44,55 Shortening of the NTR led to unconventional, ATP-dependent, Brr2-mediated tri-snRNP disruption into U4/U6 di-snRNP and U5 snRNP, 55 and removal of the first 120 residues of the NTR in yeast Brr2 elicited an increased loss of U5 and U6 snRNAs during spliceosome activation. 44 Similar to the CC, Y2H 54 and pulldown studies 44 suggested that the NTR interacts with a large number of splicing factors implicated in different steps of splicing, consistent with the NTR supporting recruitment or anchoring of Brr2 to U5 snRNP and the tri-snRNP. 55 The diverse protein interactions of the NTR might help to reinforce, fine-tune or release Brr2 auto-inhibition via the NTR.…”
Section: Layer III -The Ntr As An Auto-inhibition Devicementioning
confidence: 99%
See 2 more Smart Citations
“…Residues 258-273, which we term the "intercassette (IC) clamp," adopt an extended conformation with a central 90°bend and laterally tape the helicase cassettes together. Residues 284-393 form a PWI domain (Absmeier et al 2015) that is connected to neighboring elements by flexible linkers and is held above the IC clamp by crystal packing contacts. Finally, residues 420-474 embrace the N-terminal cassette, resembling an "N-terminal cassette (NC) clamp."…”
Section: The Brr2 Ntr Interlocks the Two Helicase Cassettesmentioning
confidence: 99%